Nanofiltration performance to remove microcystins from water for human consumption at a pilot scale - Serrão Sousa, Vânia (2010)
The presence of microcystins (MC) in drinking water reservoirs, even at low concentrations, is a problem for all involved in management and water treatment. This cyclic peptide hepatotoxin, produced by several species of toxic cyanobacteria as secondary metabolites, cause liver damage and is considered tumor promoter (Matsushima et al., 1992), representing a potential hazard to human health (Carmichael, 1994). Therefore, it is necessary to ensure their removal in water treatment plants (WTP) by innovative and effective treatments. In recent years, nanofiltration (NF) has become an attractive alternative technology to conventional water treatment due to the capacity to remove inorganic and organic compounds (disinfection by-products (DBP) precursors) with low molecular weight cut-offs and low operating pressures (Her et al., 2000; Costa and Pinho, 2006). However, the application of NF to drinking water treatment is affected by natural organic matter (NOM) fouling (Hong and Elimelech, 1997). Membrane fouling refers to plugging and external pore blocking (Gwon et al., 2003) which causes low performance and reduction of membrane time life, because of flux decline and/or transmembrane pressure increase (Her et al., 2000). In addition, good results were obtained with NF to remove cyanotoxins present in water for human consumption. According to some authors (Ribau Teixeira and Rosa, 2005; Gijsbertsen- Abrahamse et al., 2006; Ribau Teixeira and Rosa, 2006), NF removed cyanobacterial toxins from water, with removal rates greater than 99% at laboratory scale. However, pilot scale experiments in real context are missing. The aim of this work is to study NF performance to remove microcystins from natural water, at a pilot scale in a real context of WTP.